Effect of Process Variables, Adsorption Kinetics and Equilibrium Studies of Hexavalent Chromium Removal from Aqueous Solution by Date Seeds and its Activated Carbon by ZnCl2 - Theydan, Samar K. (Iraqi Journal of Chemical and Petroleum Engineering, 2018)
The adsorption of hexavalent chromium by preparing activated carbon from date seeds with zinc chloride as chemical activator and granular date seeds was studied in a batch system. The characteristics of date seeds and prepared activated carbon (ZAC) were determined and found to have a surface area 500.01 m2/g and 1050.01  m2/g , respectively and  iodine number of 485.78 mg/g and 1012.91  mg/g, respectively. The effects of PH value (2-12), initial sorbate concentration(50-450mg/L), adsorbent weight (0.004-0.036g) and contact time (30-150 min) on the adsorption process were studied . For Cr(VI) adsorption on ZAC, at 120 min time contact, pH solution 2 and 0.02  adsorbent  weight  will achieve an amount of 35.6 mg/g adsorbed  . While when use date seeds as adsorbent , conditions of 3 solution pH, 0.02 absorbent  weight , and 120 contact time gave  26.49 mg/g adsorbed amount. Using both Langmuir, Freundlich and Sips models were explain the dsorption isotherms. It declare  that the Sips model fits well with the experimental data with a maximum  Cr( VI) adsorption capacity for (ZAC) and granular date stone 233.493 and  208.055  mg/g, respectively . The kinetics data which obtained at different initial Cr(VI)  concentrations  were examined by using pseudo-first-order, pseudo-second-order, and intra-particle diffusion models . The result gained showed that the second-order model was only describing well the empirical kinetics data of both (ZAC) and granular date seeds. It was noticed that the granular date seeds has   adsorption performance lower than the (ZAC).